Effectiveness of The Antibacterial Activity on Orthosiphon aristatus Leaves Extract Against Proteus mirabilis and Staphylococcus saprophyticus: Uji Efektivitas Antibakteri Ekstrak Daun Kumis Kucing (Orthosiphon aristatus) Terhadap Bakteri Proteus mirabilis dan Staphylococcus saprophyticus - Nisak, Khairun; Rini, Chylen Setiyo (Medicra (Journal of Medical Laboratory Science/Technology), 2021)
Orthosiphon aristatus is traditional medicinal plants. Orthosiphon aristatus leaves contain alkaloid, saponin, steroid, triterpenoid, and phenolic which are antibacterial compounds. Proteus mirabilis and Staphylococcus saprophyticus can cause urinary tract infections. This study aims to determine the optimum concentration of Orthosiphon aristatus leaves extract against Proteus mirabilis and Staphylococcus saprophyticus. This research is an experimental study. This research was carried out in the Bacteriology laboratory of the Muhammadiyah University of Sidoarjo. Antibacterial activity test of Orthosiphon aristatus leaves extract used the disc diffusion method at a concentration of 25%, 50%, 75%, 100%. This test is performed 3 times. Measurement of the diameter of the zone of inhibition is measured using a caliper. The data obtained were tested statistically with Anova with a significant level of 0.05 (5%). The results showed that the Orthosiphon aristatus leaves at a concentration of 25%, 50%, 75%, 100% had a significant effect on Proteus mirabilis with an average of 6.22 mm, 9.36 mm, and 15.55 mm, 21.22 mm and Staphylococcus saprophyticus with a mean of 5.4 mm, 8.8 mm, 14.53 mm, and 20.71 mm.